(untitled) (Revista científica Olimpia, 2015)
The current professional training requires a teaching of basic mathematics that not only contributes to the development of logical thinking but understanding the world and the surrounding environment from the own professional situations, as well as building skills and reconstruct new knowledge; what it means to develop these skills, habits and basic skills for observing, collecting, data processing and analysis of the results, so that scientific training is achieved, from the potential offered mathematical knowledge. Through this research the potentialities of modeling contexts and professional situations of sport and everyday life in the training of freshmen in the career of Physical Culture, aspects that contribute to improve the creativity and exploits their independence. It has been successfully applied in the first year in the career of physical culture and in the 10th grade of senior high schools of the municipality Bayamo.